2020
DOI: 10.1177/0269215520943650
|View full text |Cite|
|
Sign up to set email alerts
|

The blood flow restriction training effect in knee osteoarthritis people: a systematic review and meta-analysis

Abstract: Objective: To synthesize evidence on the effects of blood flow restriction (BFR) comparing with high (HLT) and low load (LLT), and on the influence of different forms of application in individuals with knee osteoarthritis. Data sources: The CENTRAL, PEDro, PubMed and BVS, which include Lilacs, Medline and SciELO, until April 2020. Review methods: A systematic review and meta-analysis of randomized trials used the PRISMA guidelines, whose main keywords were: Therapeutic Occlusion, Resistance Training, and Knee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
0
17
0
4
Order By: Relevance
“…These findings are well in line with previous literature reporting the positive influence of increased muscle mass and strength on subjective pain perception and QoL in OA-affected patients ( Davison et al, 2017 ; Kemnitz et al, 2017 ). A meta-analysis by Ferlito et al (2020) ) was able to show that BFRE leads to similar gains in muscle mass and strength with concurrent reductions in perceived pain like high-intensity training. Although there is no high-intensity comparison group in the current study, our data are well in line with previous reports showing that low-intensity exercise with BFR is superior to low-intensity exercise alone ( Segal et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are well in line with previous literature reporting the positive influence of increased muscle mass and strength on subjective pain perception and QoL in OA-affected patients ( Davison et al, 2017 ; Kemnitz et al, 2017 ). A meta-analysis by Ferlito et al (2020) ) was able to show that BFRE leads to similar gains in muscle mass and strength with concurrent reductions in perceived pain like high-intensity training. Although there is no high-intensity comparison group in the current study, our data are well in line with previous reports showing that low-intensity exercise with BFR is superior to low-intensity exercise alone ( Segal et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear need for further interventional studies of BFRT in tendinopathy and tendon rupture rehabilitation, with high quality large scale RCTs required to reach definitive conclusions and recommendations for BFRT in tendon pathology. However, there is a clear scientific rationale for the potential of clinical improvements in tendon pathology with BFRT as evidenced by the beneficial effects seen in healthy tendons, and the improvement of clinical outcomes with BFRT in other musculoskeletal disorders (Ohta et al, 2003 ; Bryk et al, 2016 ; Giles et al, 2017 ; Ferraz et al, 2018 ; Korakakis et al, 2018a ; Ferlito et al, 2020 ; Grantham et al, 2021 ). Given the increased research interest and clinical use of BFRT in musculoskeletal rehabilitation for non-tendon pathologies, the dearth of available studies applying BFRT to tendon pathologies could be considered somewhat surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst traditional eccentric or HSRT for tendinopathy utilizes heavy training loads of up to 70% of 1 repetition maximum (1-RM), low-load BFRT (LL-BFRT) typically uses lower training intensities, and loads in the range of 20–40% of 1RM, which may be more tolerable for patients not able to tolerate high muscle-tendon training loads, while still preventing muscle atrophy and promoting hypertrophy (Centner et al, 2019a ; Krzysztofik et al, 2019 ; Shiromaru et al, 2019 ; Kataoka et al, 2022 ). Interventional studies have found superior or similar clinical outcomes with LL-BFRT compared to conventional high-load resistance training (HL-RT) in knee rehabilitation for ACL reconstruction, patellofemoral pain, and knee osteoarthritis (Ohta et al, 2003 ; Bryk et al, 2016 ; Giles et al, 2017 ; Ferraz et al, 2018 ; Korakakis et al, 2018a ; Ferlito et al, 2020 ; Grantham et al, 2021 ). BFRT has been shown to cause exercise-induced hypoalgesia through endogenous opioid and endocannabinoid mechanisms, so could therefore be a useful pain management tool in early musculoskeletal rehabilitation, particularly in the presence of an acute pain response (Korakakis et al, 2018b ; Hughes and Patterson, 2019 , 2020 ; Hughes et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its efficacy while using low-load resistance, it may be beneficial in elderly populations with more physical limitations due to OA or generalized muscle atrophy. A recent meta-analysis observing BFRT in patients with knee OA concluded that BRFT is a reasonable intervention for improving muscle strength and volume with low mechanical stress [ 19 ]. With promising data from current studies, a clear need for expanded research of BFRT after total knee arthroplasty is indicated [ 9 ].…”
Section: Blood Flow Restriction Therapymentioning
confidence: 99%